Total factor productivity and sources of long-term growth in Indian agriculture - Rosegrant, Mark W.; Evenson, Robert E. (International Food Policy Research Institute, 1995)
This paper assesses total factor productivity (TFP) growth in India, examines the sources of productivity growth, including public and private investment, and estimates the rates of return to public investments in agriculture. The results show that significant TFP growth in the Indian crops sector was produced by investments -- primarily in research -- but also in extension, markets, and irrigation. The high rates of return, particularly to public agricultural research and extension, indicate that the Government of India is not overinvesting in agricultural research and investment, but rather that current levels of public investment could be profitably expanded.